2018
DOI: 10.1111/pan.13365
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Narcotrend™ EEG‐guided propofol administration on the speed of recovery from pediatric procedural sedation—A randomized controlled trial

Abstract: Narcotrend Index guidance of propofol delivery for deep sedation in children aged 12-17 years, underdoing gastrointestinal endoscopy results in faster recovery, less drug consumption, and fewer episodes of oversedation than dosing propofol according to clinical surrogate parameters of depth of hypnosis. The results of this study provide additional evidence in favor of the safety profile of propofol/remifentanil for procedural sedation in adequately selected pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
2
12
1
1
Order By: Relevance
“…18–21 Seven randomized controlled trials investigated EEG-guidance during anesthesia, 11,25,30 several of which demonstrated benefit. 11,27–29 Eight observational studies 9,10,31–35 demonstrated usefulness of EEG-guided anesthesia in children, and 32 observational studies described anesthesia-induced changes in children’s brains. 37–68 (Supplemental Digital Content 2, Table, http://links.lww.com/AA/E82, provides a summary and key findings of the 59 papers that underwent full-text review.)…”
mentioning
confidence: 99%
“…18–21 Seven randomized controlled trials investigated EEG-guidance during anesthesia, 11,25,30 several of which demonstrated benefit. 11,27–29 Eight observational studies 9,10,31–35 demonstrated usefulness of EEG-guided anesthesia in children, and 32 observational studies described anesthesia-induced changes in children’s brains. 37–68 (Supplemental Digital Content 2, Table, http://links.lww.com/AA/E82, provides a summary and key findings of the 59 papers that underwent full-text review.)…”
mentioning
confidence: 99%
“…9,20 Weber et al showed lower consumption of anaesthetic agents and faster awakening after the procedure in randomized controlled trial with Narcotrend in children's anaesthesia for endoscopic procedures. 21 Another device worth applying is SedLine monitor, which is based on 4-channel EEG, separately monitoring both hemispheres. Apart from the global patient state index (PSI), whose reference value during administering general anaesthesia should be between 25 and 50, the analysis encompasses also the spectral density of EEG wave from over both hemispheres.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, there are evidences supporting the value of Narcotrend in titrating drug dosages both in the adult and paediatric population in the operating room and the non-operating room setting 39–44…”
Section: Discussionmentioning
confidence: 99%